2014
DOI: 10.1186/1477-7525-12-25
|View full text |Cite
|
Sign up to set email alerts
|

The role of quality of care and attitude towards disability in the relationship between severity of disability and quality of life: findings from a cross-sectional survey among people with physical disability in China

Abstract: BackgroundPeople with physical disability (PWPD) is the largest subgroup of people with disability (PWD) in China, but few studies have been conducted among this vulnerable population. The objective of this study was to investigate the level of quality of life (QoL), self-perceived quality of care and support (QOCS), severity of disability and personal attitude towards disability among people with physical disability in China, as well as to identify how QoL can be affected by severity of disability through QOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 39 publications
1
30
0
3
Order By: Relevance
“…Therefore, professionals should critically reflect and discuss with their peers their own attitudes, perceptions and practices to ensure they are serving their clients in a non-stigmatising fashion. Holding negative attitudes jeopardises quality of care (Zheng et al 2014 ) and may deter families from accessing services. Finally, given how autism stigma manifests in different degrees and types across cultures, it will be of benefit to families if the professionals they access are culturally competent; otherwise they may be rejected and/or distrusted.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, professionals should critically reflect and discuss with their peers their own attitudes, perceptions and practices to ensure they are serving their clients in a non-stigmatising fashion. Holding negative attitudes jeopardises quality of care (Zheng et al 2014 ) and may deter families from accessing services. Finally, given how autism stigma manifests in different degrees and types across cultures, it will be of benefit to families if the professionals they access are culturally competent; otherwise they may be rejected and/or distrusted.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported the courtesy stigma exhibited by caregivers of PWD [ 16 18 ]; however, because this stigma is only one component of a complex of attitudes, few studies reported PWD family-member caregivers’ attitudes in Chinese society. Generally, a negative attitude can undermine the quality of assistance and support, thus decreasing PWD’s quality of life [ 19 ] and inhibiting PWD integration into the community. Lower prospects for the disabled may lead to maladaptive coping and inconsistent rehabilitation or treatment [ 20 ] and greater strain on both PWD and caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…A rede de apoio de pessoas com deficiência influencia a percepção do cuidado e a incapacidade das pessoas com deficiência 7 . O nível de percepção de pessoas com deficiência física acerca de sua rede de apoio é fortalecido por relações familiares e também por pessoas próxima [8][9][10] .…”
Section: Revisão De Literaturaunclassified